The thermoluminescence response of undoped Silica PCF for dosimetry application - Ghomeishi, M.; Mahdiraji, G.A.; Adikan, Faisal Rafiq Mahamd; Hashim, S. (IEEE, 2013)
This work concerns the suitability of the undoped silica photonic crystal fibre (PCF) as ionizing radiation dosimeters. The dosimetric capabilities of PCF optical fibres in terms of thermoluminescence (TL) and dose response have been investigated and compared with the single mode fibre (SMF) subjected to 6 MeV electron irradiations. The PCF shows dose response linearity curves in a dose range familiar to conventional radiation therapy covering doses from 1 to 4Gy.